ISLAMIC COMMUNITY DEVELOPMENT BASED ON NATURAL RESOURCE (NR) ASSET EMPOWERMENT IN PONGGOK VILLAGE, POLANHARJO, KLATEN - Hidayah, Sri Noor Mustaqimatul; Saliyo, Saliyo; Qodarsasi, Umi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to reveal the implementation of Islamic Community development based on the empowerment of Natural Resources (NA) assets in Ponggok Village, Polanharjo, Klaten. This research on the development of an Islamic Community based on the empowerment of Natural Resources (NA) assets was carried out using a qualitative approach with the type of field research with data collection techniques using interview, observation, and documentation techniques. The results showed that the development of an Islamic Community based on asset empowerment in Ponggok Village, Polanharjo, Klaten was carried out by; (1) Exploring the natural potential of Ponggok Village which is used as a tourist attraction for Umbul Ponggok, (2) Development of the Umbul Ponggok tourist area through BUMDes Tirta Mandiri, and (3) Marketing strategy of the Umbul Ponggok tourist area through social media. The current achievements obtained by Ponggok Village in developing the potential of natural resources cannot be separated from the cooperation of the village government, the tourism office, and residents to boost the standard of living of the people in it and improve the quality of better tourism through the development of natural resource potential. Suggestions for further researchers to conduct research in Ponggok Village with other studies, In addition, to conduct research related to the development of natural resources in other areas.